To form children health behaviour during the Covid-19 Pandemic: Teacher's strategy and obstacle - Dedy Surya (Institut Agama Islam Negeri Langsa, 2020)
The Covid-19 pandemic is forcing everyone to change their behaviour to become more concerned about their health. This study aimed to illustrate the teachers’ strategy and the obstacle in shaping health behaviours of children in school. By using a qualitative approach, the data was collected through in-depth interviews involving 9 participants (6 teachers and 3 parents). The results showed that to shape health behaviour, the teachers formed a conducive environment through a commitment with parents to implement a healthy lifestyle. This health behaviour campaign was carried out through creative means such as using stories and singing regularly and consistently. The teacher also engages other pupils to reprimand the child who committed the offence. This conducive environment will support the formation of health behaviours. Conversely, incompatible environments such as lack of facilities and the parent's inconsistency in at home intervening behaviour will damage the habits that have been established at school.